Cores, peripheries, and globalization : essays in honor of Ivan T. Berend - Berend, T. Iván (Tibor Iván), 1930-; Reill, Peter Hanns; Szelényi, Balázs A. (Central European University Press, 2011)
Deals with the intersection of issues associated with globalization and the dynamics of coreperiphery relations. It places these debates in a large and vital context asking what the relations between cores and peripheries have in forming our vision of what constitutes globalization and what were and are its possible effects. In this sense the debate on globalization is framed as part of a larger and more crucial discourse that tries to account for the essential dynamics-economic, social, political and cultural-between metropolitan areas and their peripheries.